A human-specific long noncoding RNA regulator of antigen-presenting cell viability and antimicrobial defense - Alexander J. Westermann; Alexandra Schock; Diyaa Al Din Ashour; Sarah Wende; Chrysanthi Skevaki; Elisabeth Mack; Bernd Schmeck; Uwe Linne; Thomas Herrmann; Nikolaos Antonakos; Helena Florou; Evangelos J. Giamarellos-Bourboulis; et al. (Proceedings of the National Academy of Sciences, 2026)
Macrophages are essential for both, to clear pathogens and preserve tissue homeostasis, yet the molecular regulators of this equilibrium remain incompletely defined. Here, we identify SAILR (survival associated immune-regulatory RNA), a primate-specific long noncoding RNA (lncRNA), as a critical modulator of macrophage viability under infection conditions. SAILR is induced during monocyte-to-macrophage differentiation, but rapidly downregulated upon bacterial challenge in a nuclear factor kappa B (NF-κB) dependent manner. In both naïve and immune-activated macrophages, SAILR dampens the expression of adhesion, phagocytosis, and invasion factors, which include SIGLEC1 and MMP7. During infection with Salmonella Typhimurium, depletion of SAILR sensitizes macrophages to apoptosis, resulting in loss of intracellular replication niches and reduced bacterial recovery. Conversely, enforced SAILR expression promotes macrophage survival and increases intracellular pathogen burden. Mechanistically, SAILR interacts with the antiapoptotic adaptor protein 14-3-3β to support macrophage survival. Notably, downregulation of SAILR is mirrored in circulating immune cells from patients with severe COVID-19 and sepsis. Together, our findings position SAILR as a central regulator in linking macrophage survival to host–pathogen interaction and disease pathophysiology.